Remote Feelings: On Blind-Sighted Collaborations and Long-Distance Art Making - David Johnson; Florian Grond (Disability Studies Quarterly, 2018)
This essay is an account of Remote Feelings, a collaborative art project conceived of by the authors in 2016. Shaped by sensory difference, remote location and the use of digital technology, namely 3D scanning and printing technology, this project, like this essay, explores haptic experience, the pairing of analogue and digital methods, and the work and influence of Austrian artist and innovator Raoul Hausmann (1886-1971). The essay also shares information on our individual artistic practices and preoccupations, including Florian Grond's use of digital information as a starting point for the exploration of sensory experience and David Johnson's use of his blindness to inform his search for a new aesthetics.